HGG-06. PODOPLANIN POSITIVE MYELOID CELLS PROMOTE GLIOMA DEVELOPMENT BY IMMUNE SUPPRESSION. (23rd April 2019) - Eisemann, Tanja; Costa, Barbara; Peterziel, Heike; Angel, Peter
Abstract: The diverse tumor microenvironment is a significant parameter in tumor development and therapy response. One compartment of the tumor microenvironment that has gained growing interest is the immune system. As endogenous defense machinery the immune system has the capacity to fight against cancer cells. However, tumor cells frequently engage immune-regulatory mechanisms to disable tumor-directed immune responses. Thus, in order to unleash the immune system against cancer cells, it is crucial to characterize in great detail individual tumor-associated immune cell populations and their role in immune evasion. In this study we investigated the function of a tumor-associated myeloid cell subpopulation characterized by podoplanin (PDPN) expression on the development of high-grade glioma tumors. The cell surface protein PDPN has frequently been associated with malignant progression in glioma and other cancer entities. In addition to tumor cells, multiple cell types in the glioma microenvironment have been reported to express PDPN, including glioma-associated myeloid cells. Interestingly, although PDPN expressing inflammatory macrophages have been shown to critically regulate inflammation during sepsis and acute respiratory distress syndrome, the function of PDPN-positive macrophages in cancer has remained unexplored. Here, we show that the deletion of Pdpn in myeloid cells results in increased CD3 + and CD8 + T-cell infiltrates and significantly prolonged survival in a syngeneic transplantation model of high-grade glioma. In vitro co-culture of glioma cell lines and macrophages revealed that PDPN transcriptionally regulates arginase-1, a well-known player in myeloid cell-mediated immune suppression. These findings identify PDPN-positive myeloid cells as one novel mediator of glioma-induced immune suppression. More detailed in vivo studies will be required to identify the underlying mechanisms and determine whether targeted ablation of PDPN-positive myeloid cells could be included in combinatorial cancer therapies to enhance immune-mediated elimination of highly aggressive and difficult to treat glioma tumors.